THE HISTORY OF SEARCH ING METHODS OF SELECTIVE NUTRIENT MEDIA PREPARATION FOR MYCOPLASMAS CULTIVATION - Berdnik, V. P.; Berdnik, I. Yu.; Ushkalow, V. O. (Scientific Progress & Innovations, 2020)
The results’ analysis obtained in searching of selective nutrient mycoplasmal media (SNMM) for the period of 120 years and published by several generations of scientists from different countries of the world, including the authors of this article, is presented. Mycoplasma, the causative agent of contagious cattle pleuropneumonia, was first cultivated by E. Nocard, E. R. Roux et al. (1898) in beef – extract broth (BEB) that was embedded in a collodion bag and sewn into the rabbit peritoneal cavity. The first variants of the medium were based on BEB or on Marten’s broth and the blood serum of animals, mainly horses. D. G. Edward (1947) suggested to add yeast extract to the media. R. M. Chanock et al. (1962) introduced the horse blood serum, yeast extract, lactalbumin hydrolyzate and DNA into the medium. It was the first time that they had cultivated the causative agent of the so –called human atypical pneumonia, Eaton agent, which was considered a virus. It was a powerful impetus to further studying mycoplasma properties and features of the diseases caused by them − mycoplasmosis of humans, animals, birds, reptiles, fish, arthropods, and plants. A number of methods have been suggested to diagnoze mycoplasmoses: from microbiological (mycoplasmological, cultural) to genetic and molecular types of polymerase chain reaction (PCR). But only mycoplasmic is the basic method –“gold standard”, all the rest are additional. Only with its help it is possible to obtain mycoplasma cultures, to study their biological properties, to make diagnostics and vaccines from them. With this purpose, it is necessary to have SNMM, that would provide mycoplasmas with plastic material and energy, and to know the conditions for their successful cultivation. M. penetrans culture was isolated by S.C.Lo et al. (1991, 1992) from human urine samples infected with the immunodeficiency virus, 29 years after the identification of the Eaton agent. It has led to the thought that, although more than 200 species of Mollicutes class have been cultivated at present, they are only part of the total number existing in nature. Therefore, their search in different hosts should be continued, but using more improved SNMM. Several hundreds have been tested with this aim and it has been concluded that it is impossible to produce a universal medium for all the species described, because they have different nutritional and cultivation conditions and requirements. Certain media meet the requirements of a few species only. Phytoplasma for Haemobartonella and Eperythrozoon cannot be cultivated in vitro so far.